Voter Preference in Local Election (Sample of Elazig Voters in 29 March Local Election) - Dogan, Adem; Goker, Goksel (Eskisehir Osmangazi Univ, Fac Education, 2010)
Voters, while the vote in local and general elections are influenced by different factors. Consequently, the preference and voting behavior has been determined. In this study intended to uncover that effect level of affect factors to voters preference and in the process of local election, what kind of factors wheter take into consideration or not by voters in the 29 March 2009 local elections. In this context, survey applied with 1000 voters in Elazig centre and so analysis to affected factors to voters preference. Obtained survey data was analysed with SPSS package program. Voters take into consideration different actors in local elections compared to general elections is an event that comes at the begining of main indication of this study.
Keywords: Local elections; voter preference; politics; public opinion; voters preference in Elazig